High degree of pharmacokinetic compatibility exists between the five-herb medicine XueBiJing and antibiotics comedicated in sepsis care - Jian Li; Olajide E. Olaleye; Xuan Yu; Weiwei Jia; Junling Yang; Chuang Lu; Songqiao Liu; Jingjing Yu; Xiaona Duan; Yaya Wang; Kai Dong; Rongrong He; et al. (Elsevier, 2019)
Managing the dysregulated host response to infection remains a major challenge in sepsis care. Chinese treatment guideline recommends adding XueBiJing, a five-herb medicine, to antibiotic-based sepsis care. Although adding XueBiJing further reduced 28-day mortality via modulating the host response, pharmacokinetic herb-drug interaction is a widely recognized issue that needs to be studied. Building on our earlier systematic chemical and human pharmacokinetic investigations of XueBiJing, we evaluated the degree of pharmacokinetic compatibility for XueBiJing/antibiotic combination based on mechanistic evidence of interaction risk. Considering both XueBiJing‒antibiotic and antibiotic‒XueBiJing interaction potential, we integrated informatics-based approach with experimental approach and developed a compound pair-based method for data processing. To reflect clinical reality, we selected for study XueBiJing compounds bioavailable for drug interactions and 45 antibiotics commonly used in sepsis care in China. Based on the data of interacting with drug metabolizing enzymes and transporters, no XueBiJing compound could pair, as perpetrator, with the antibiotics. Although some antibiotics could, due to their inhibition of uridine 5'-diphosphoglucuronosyltransferase 2B15, organic anion transporters 1/2 and/or organic anion-transporting polypeptide 1B3, pair with senkyunolide I, tanshinol and salvianolic acid B, the potential interactions (resulting in increased exposure) are likely desirable due to these XueBiJing compounds' low baseline exposure levels. Inhibition of aldehyde dehydrogenase by 7 antibiotics probably results in undesirable reduction of exposure to protocatechuic acid from XueBiJing. Collectively, XueBiJing/antibiotic combination exhibited a high degree of pharmacokinetic compatibility at clinically relevant doses. The methodology developed can be applied to investigate other drug combinations. Key Words: XueBiJing, Antibiotic, Combination drug therapy, Sepsis, Pharmacokinetic compatibility, Herb‒drug interaction